Concise Synthesis of the Terpene Core Structure of Suaveolindole through a Time-Economic Route - Tanimoto, Hiroki; Tojo, Kazuki; Morimoto, Tsumoru; Kakiuchi, Kiyomi (Synlett, 2021)
The terpene core structure of suaveolindoles was synthesized through a concise route in a time-economical manner. A scalable synthetic route from pulegone delivered the desired α,β,γ,δ-unsaturated ester in a brief period. By way of Eschenmoser–Claisen rearrangement, carbon side-chain moiety at the crowded double-allylic position was introduced stereoselectively.
Keywords: terpene; time-economy synthesis; natural product synthesis; Claisen rearrangement; DFT calculation